Experience in the use of MRI-ultrasound fusion-targeted biopsy of the prostate for the diagnosis of prostate cancer - E. S. Nevirovich; O. Yu. Shestopalova; A. A. Yakovenko; A. Sh. Rumiantsev; Yu. V. Matveeva (Вестник хирургии имени И.И. Грекова)
The objective of this study was to compare the results of the MRI-ultrasound fusion-targeted biopsy (MRF-TB) and the systematic 12-core biopsy (SB) of the prostate and investigate the relationship between the results of the biopsy and the multiparametric MRI of the prostate before the biopsy.Material and methods. The study included 380 men with a total PSA level from 4 to 10 ng/ml (according to Hybritech calibration) and with negative result of finger rectal examination at the age from 45 to 80 years. All men underwent a multiparametric MRI of the prostate before biopsy. The changes detected on the MRI were assessed taking into account the PI-RADS Version 2-criterion. All men (247 men) with PI-RADS 2 or more underwent MRF-TB (4 aiming columns) and SB (12 standard points) of the prostate.Results. There were no significant differences in the detection of all types of prostate cancer (PC) in all patients between MRF-TB and SB (p=0.731). At the same time, significantly less PC (Gleason 6) (p<0.001) and significantly more PC (Gleason ≥7) (p<0.001) were detected with MRF-TB compared with SB. Also, MRF-TB allows significantly more often to detect the most malignant form of PC (Gleason ≥4+3) compared with SB (p=0.025).Conclusion. MRF-TB detects more cases (Gleason ≥7), compared with SB, while limiting the detection of PC (Gleason 6) in all men presented for biopsy of the prostate.